2015
DOI: 10.1002/ece3.1388
|View full text |Cite
|
Sign up to set email alerts
|

Naturally rare versus newly rare: demographic inferences on two timescales inform conservation of Galápagos giant tortoises

Abstract: Long-term population history can influence the genetic effects of recent bottlenecks. Therefore, for threatened or endangered species, an understanding of the past is relevant when formulating conservation strategies. Levels of variation at neutral markers have been useful for estimating local effective population sizes (Ne) and inferring whether population sizes increased or decreased over time. Furthermore, analyses of genotypic, allelic frequency, and phylogenetic information can potentially be used to sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
32
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 119 publications
(273 reference statements)
12
32
4
Order By: Relevance
“…Another cause of heterozygote deficit can be the mating of close relatives, leading to an increase in homozygosity. Here, we found the adult sample to have a significant F is value, which is consistent with other studies that have found the Pinzón population to have inbreeding coefficients higher than many of the other populations of Galá-pagos tortoise (Garrick et al 2015). Given the recent decrease in population size and its currently small size, inbreeding is also a plausible explanation for the observed heterozygote deficit.…”
Section: In Situ Diversitysupporting
confidence: 92%
See 1 more Smart Citation
“…Another cause of heterozygote deficit can be the mating of close relatives, leading to an increase in homozygosity. Here, we found the adult sample to have a significant F is value, which is consistent with other studies that have found the Pinzón population to have inbreeding coefficients higher than many of the other populations of Galá-pagos tortoise (Garrick et al 2015). Given the recent decrease in population size and its currently small size, inbreeding is also a plausible explanation for the observed heterozygote deficit.…”
Section: In Situ Diversitysupporting
confidence: 92%
“…Yet, simulation studies have shown that the M-ratio test may be more robust than heterozygosity-based approaches for detecting bottlenecks under a number of scenarios including when a population has made a demographic recovery, mutation rates are high, or pre-bottleneck sizes were large (Williamson-Natesan 2005). The latter case may be relevant for C. ephippium, as recent reconstructions based on slower-evolving mitochondrial DNA and a nuclear intron (PAX-P1) revealed that Pinzón tortoises had a very large historical effective population size that was increasing over the last 8000 generations (Garrick et al 2015). This work built upon an earlier study using mitochondrial DNA (Beheregaray et al 2003a) that likewise detected signatures of demographic expansion in Pinzón tortoises based on mismatch distributions.…”
Section: In Situ Diversitymentioning
confidence: 96%
“…In particular, genomescale variation data allows for inference of demographic factors such as population size changes, the timing and ordering of population splits, migration rates between populations, and the founding of admixed populations (Pool et al 2010;Pickrell and Pritchard 2012;Sousa and Hey 2013). Such efforts can refine our picture of demographic events inferred from the archaeological record (e.g., Fagundes et al 2007;Goebel et al 2008), or reveal such events in species where no archaeological data are available, and can aid conservation efforts by complementing census data (e.g., Hájková et al 2007;Garrick et al 2015).Population genomic data sets are well suited for this task simply because demographic changes leave their mark on patterns of genetic variation. Recent population growth, for example, will result in an excess of rare variation compared to equilibrium expectations (Fu 1997), while population contraction will result in an excess of intermediate frequency alleles (Maruyama and Fuerst 1985).…”
mentioning
confidence: 99%
“…Galápagos giant tortoises are endemic to the Galápagos Islands and are currently recognized as an endangered, multi-species complex including both extant and extinct taxa. Taxonomic definitions are based on morphology, geographic isolation and population genetic evidence based on short DNA sequences of the mitochondrial genome (mtDNA) and/or a dozen or so nuclear microsatellite loci [5][6][7][8]. The species complex enjoys maximal protection.…”
mentioning
confidence: 99%